Goodwill in passing off : a common law perspective - Ng, Catherine W. (Elgar monographs in intellectual property law series, 2021)
"The law of passing off protects traders from a form of misrepresentation that harms their goodwill, and consumers from the market distortion that may result. This carefully-crafted work seeks to delineate two intertwined aspects of goodwill: substantive and structural goodwill. It argues that the law of passing off should focus on protecting structural goodwill, and that this in turn allows traders' authentic voices to help shape the substantive goodwill to attract custom for them in the marketplace. The author clarifies the concept of 'goodwill', and examines this concept in the context of the common law jurisdictions of Australia, Canada, England and Wales as well as of relevant case law under ℗ʹ43(a)(1)(A) of the US Lanham Act. The book analyses the application of the law of passing off within the multi-directional social exchanges that traders, consumers and commentators engage in, as well as challenges the current consumer search costs theory that underpins the law of passing off and trademark laws. Providing a fresh look at this ever-changing aspect of law, this book will be key reading for legal scholars and students for its examination of inconsistencies in current law. Legal practitioners will also find this an invaluable resource as it considers the diverse application of the law"--